Spirits and slaves in central Sudan : the red wind of Sennar - Kenyon, Susan M. (Contemporary anthropology of religion., 2012)
This historical ethnography of Central Sudan explores the century-old intertwining of zar, spirit possession, with lives of ex-slaves. Despite very different social and cultural contexts, it has continued to be shaped by the experience of slavery. As the treatment of last resort, zar addresses a wide range of problems brought predominantly by women through participation in colorful and often opaque ritual events. Drawing on field research spanning three decades and laced with participants' own narratives, Kenyon shows how zar continues to embody subaltern memories of Ottoman Egypt, which shape and support the structure of contemporary beliefs and practices. At the same time, it is the effective articulation of these memories, with the impact of global capitalism and shifting Islamic realities (both political Islam and Sufism), that accounts for zar's ongoing popularity.